Study on the Necessity and Methodology for Enhancing Outpatient and Clinical Education in the Department of Radiology - Soo Buem Cho; Jiwoon Seo; Young Hwan Kim; You Me Kim; Dong Gyu Na; Jieun Roh; Kyung-Hyun Do; Jung Hwan Baek; Hye Shin Ahn; Min Woo Lee; Seunghyun Lee; Seung Eun Jung; et al. (Journal of the Korean Society of Radiology)
In the rapidly evolving healthcare environment, radiologists strive to establish their rightful place. Thus, there is a need for enhanced outpatient and clinical education within the Department of Radiology and exploration of its methodologies. Accordingly, the Korean Society of Radiology established a task force to investigate the clinical and outpatient practice status of radiologists overseas, current state of related education, involvement of other specialties in radiologic practices and education in Korea, and clinical and outpatient practice status among Korean radiologists. Furthermore, a survey on clinical competency enhancement was conducted among the members of the Korean Society of Radiology. These findings suggest the need for visibility and clinical competency enhancement in radiologists and methodologies for strengthening clinical competencies.